Boosting the Productivity of H2-Driven Biocatalysis in a Commercial Hydrogenation Flow Reactor Using H2 From Water Electrolysis - Poznansky, Barnabas; Cleary, Sarah E.; Thompson, Lisa A.; Reeve, Holly A.; Vincent, Kylie A. (Frontiers in Chemical Engineering, 2021)
Translation of redox biocatalysis into a commercial hydrogenation flow reactor, with in-built electrolytic H2 generation, was achieved using immobilized enzyme systems. Carbon-supported biocatalysts were first tested in batch mode, and were then transferred into continuous flow columns for H2-driven, NADH-dependent asymmetric ketone reductions. The biocatalysts were thus handled comparably to heterogeneous metal catalysts, but operated at room temperature and 1–50 bar H2, highlighting that biocatalytic strategies enable implementation of hydrogenation reactions under mild–moderate conditions. Continuous flow reactions were demonstrated as a strategy for process intensification; high conversions were achieved in short residence times, with a high biocatalyst turnover frequency and productivity. These results show the prospect of using enzymes in reactor infrastructure designed for conventional heterogeneous hydrogenations.